Emulsion Solvent Evaporation-Induced Self-Assembly of Block Copolymers Containing pH-Sensitive Block - Wu, Yuqing (Langmuir : the ACS journal of surfaces and colloids, 2017)
A simple yet efficient method is developed to manipulate the self-assembly of pH-sensitive block copolymers (BCPs) confined in emulsion droplets. Addition of acid induces significant variation in morphological transition (e.g., structure and surface composition changes) of the polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP) assemblies, due to the hydrophobic-hydrophilic transition of the pH-sensitive P4VP block via protonation. In the case of pH > pKa(P4VP) (pKa (P4VP) = 4.8), the BCPs can self-assemble into pupa-like particles because of the nearly neutral wetting of PS and P4VP blocks at the oil/water interface. As expected, onion-like particles obtained when pH is slightly lower than pKa(P4VP) (e.g., pH = 3.00), due to the interfacial affinity to the weakly hydrophilic P4VP block. Interestingly, when pH was further decreased to ∼2.5, interfacial instability of the emulsion droplets was observed, and each emulsion droplet generated nanoscale assemblies including vesicles, worm-like and/or spherical micelles rather than a nanostructured microparticle. Furthermore, homopolymer with different molecular weights and addition ratio are employed to adjust the interactions among copolymer blocks. By this means, particles with hierarchical structures can be obtained. Moreover, owing to the kinetically controlled processing, we found that temperature and stirring speed, which can significantly affect the kinetics of the evaporation of organic solvent and the formation of particles, played a key role in the morphology of the assemblies. We believe that manipulation of the property for the aqueous phase is a promising strategy to rationally design and fabricate polymeric assemblies with desirable shapes and internal structures